Carbono tipo diamante em componentes de implantes dentários: avaliação das propriedades antimicrobianas e de adesão de Escherichia coli - Maquera Huacho, Patricia Milagros [UNESP] (2014)
The study of DLC films is the subject of research due to their different properties including antibacterial properties. Rehabilitator in implant treatment, complications may occur, providing the infiltration of oral microorganisms for implant- abutmente interface. The aim of this study was to evaluate properties and wetting surface free energy from the values of the contact angle; antimicrobial properties bioadhesion and cytotoxicity of titanium discs coated with DLC. Escherichia coli was maintained on BHI at 37 ° C for 3 h and 24 h for antimicrobial test. For adhesion test, the discs were maintained in culture of E. coli for 90 minutes at 37 ° C and 20 minutes inside ultrasound. The ability to prevent the migration of bacteria into the implant - abutment interface was performed in dental implants External Hexagon connected with a torque of 32N and left in contact with E. coli for 24 h , and Polymerase Chain Reaction semi -quantitative was performed to confirm the sterility of the technique. Were quantified in CFU / ml in BHI agar for antimicrobial test, bacterial adhesion and infiltration. Cytotoxicity was performed using human keratinocytes ( HaCaT ) cultured in DMEM maintained in an atmosphere of 5% CO2 at 37 ° C and evaluated by the MTT colorimetric assay. The results of wettability, antimicrobial test, adhesion test and bacterial infiltration showed no statistically significant difference between the test groups. The surfaces of titanium and coated with DLC showed a slight decrease in cell viability with a statistically significant difference to the control group. The DLC is presented as biocompatible material with mild cytotoxicity without changing the surface properties, has no antimicrobial properties, does not interfere with bacterial adherence for E. coli and do not inhibit bacterial infiltration into the implant-abutment interface.